2023
DOI: 10.1038/s41598-023-44616-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between breakthrough infection with COVID-19 and Toxoplasma gondii: a cross-sectional study

Marwa A. Gouda,
Hind S. AboShabaan,
Ahmed S. Abdelgawad
et al.

Abstract: The breakthrough infection following COVID-19 vaccination has been a subject of concern recently. Evidence suggests that COVID-19 vaccine efficacy diminishes over time due to multiple factors related to the host, and vaccine. Coinfection with other pathogens was claimed earlier as a contributing cause for this phenomenon. Hence, we aimed to stratify the association of post-COVID-19 vaccination breakthrough coinfection with Toxoplasma gondii (T. gondii) and its impact on disease severity. This cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 33 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…et al in Mexico revealed that 21.9% of patients with COVID-19 showed the presence of T. gondii (17). Studies by Gouda MA, et al, (20) and Hasanzadeh M, et al (22) indicated the absence of active T. gondii infection in patients with COVID-19 by IgM detection.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…et al in Mexico revealed that 21.9% of patients with COVID-19 showed the presence of T. gondii (17). Studies by Gouda MA, et al, (20) and Hasanzadeh M, et al (22) indicated the absence of active T. gondii infection in patients with COVID-19 by IgM detection.…”
Section: Discussionmentioning
confidence: 97%
“…Disparities in the prevalence of toxoplasmosis in patients with COVID-19 in various studies can be attributed to environmental factors such as temperature, humidity, geographic regions, and also sociodemographic factors such as the age distribution of the population examined (20,32). A greater propensity for infection has been noted in areas with humid and warm climates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations